PENGARUH ALOKASI ANGGARAN PENDIDIKAN, PENGANGGURAN, DAN INFLASI TERHADAP KEMISKINAN DI PROVINSI SUMATERA UTARA - Bernadeth YP Simangunsong; Charitin Devi (STISIP Widyapuri Mandiri Sukabumi, 2023)
This study aims to determine the effect of education budget allocation, unemployment, and inflation on poverty in North Sumatra Province. This type of research is a quantitative study with a total sample of 21 observation periods from 2002 to 2022. The data analysis technique used multiple linear regression analysis. Multiple linear regression equation model: LnY = b0 + b1LnX1 + b2LnX2 + b3LnX3 + e. From the research results it is known that the estimated value of the multiple linear regression equation is LnJlhPendMiskin = 15.01147 – 0.069179 LnAngPend + 0.078522 LnUnemployment + 0.022907 LnInflation. This study shows that there is a negative and significant effect of the education budget on poverty (probability 0.0004 <0.05). While unemployment and inflation have no significant effect on poverty in North Sumatra Province. With a coefficient of determination of 71.66% and simultaneously the education budget variables, unemployment and inflation have a significant effect on poverty in North Sumatra Province.